2014
DOI: 10.9790/0837-19143032
|View full text |Cite
|
Sign up to set email alerts
|

Creative Thinking Ability among High School Children

Abstract: A sample of the study comprised of 300 high school children in the age group of 13-16 year from five urban high school of Dharwad taluk. Creative thinking scale developed by mehdi (1989) and creative thinking check list developed by AICRIP-CD Dharwad center (2010) were used to assess the creative thinking ability of children. The result of the study revealed that majority of children showed high level of creative thinking ability and none of them belonged to low category of creative thinking ability. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
5
1
Order By: Relevance
“…However, this result disagree with the study of Kumari, Pujar, and Naganur (2014) which revealed that majority of children showed high level of creative thinking ability.…”
Section: Resultscontrasting
confidence: 55%
“…However, this result disagree with the study of Kumari, Pujar, and Naganur (2014) which revealed that majority of children showed high level of creative thinking ability.…”
Section: Resultscontrasting
confidence: 55%
“…Except elaboration ability, no statistically significant difference was found among the age groups. Empirical evidence present in support of this finding [28], however, contradictory results also present [29,33,35], which shows not specific pattern of creativity development across ages. When grade was the concern, our results showed a clear cut increase in elaboration ability, originality and consequently overall creativity from grade/class six to class eight.…”
Section: Discussionmentioning
confidence: 84%
“…However, on the other hand, few studies reported no significant differences in children's creative abilities concerning gender, grade, and social caste [31][32][33]. Another study reported no significant differences in visual-spatial creativity between countries [34], while others observed high creative thinking ability in children unaffected by school type, age, or gender [35]. Ward and Warren identified socio-economic status but not gender as a significant factor in creativity [36].…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Table 6 shows the learning outcomes on the answered science creativity tests. A ranking system for the level of student creativity by (Abu Kasim, 2012;Kumari et al, 2014). The table aims to show the level of students' scientific creativity in the topic of waste.…”
Section: Resultsmentioning
confidence: 99%
“…In this study the level of student creativity was measured using a test item called Torrance Tests of Creative Thinking which was adapted and adopted from studies (Hu & Adey, 2002;Orozco & Yangco, 2016) which is shown in Table 3. Table 3 shows the meaning of scores to determine the level of creativity among students based on (Kumari et al, 2014). Scores from 0 to 33 indicate the lowest level of creativity.…”
Section: Instrumentmentioning
confidence: 99%